2016
DOI: 10.1074/jbc.m116.727008
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Connexin43 Function and Expression by Tyrosine Kinase 2

Abstract: Gap junctions are integral membrane proteins that enable the direct cytoplasmic exchange of ions and low molecular weight metabolites (Ͻ1 kDa) between adjacent cells. They provide an intercellular pathway for the propagation and/or amplification of signal transduction cascades triggered by cytokines, growth factors, and other cell-signaling molecules involved in growth regulation and development. Gap junctions are formed by the apposition of connexons from adjacent cells, where each connexon is formed by six c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 85 publications
1
21
1
Order By: Relevance
“…Of note, Cx32 residue Ser 233 is also associated with increased GJIC when phosphorylated (12). This finding is in contrast to tyrosine phosphorylation of the Cx43CT, as phosphorylation of Tyr 247 , Tyr 265 , and Tyr 313 is associated with decreased GJIC (10,(32)(33)(34)(35)(36). Taken together, this information suggests that phosphorylation (even by the same kinase) regulates different connexin isoforms via different mechanisms.…”
Section: Discussionmentioning
confidence: 88%
“…Of note, Cx32 residue Ser 233 is also associated with increased GJIC when phosphorylated (12). This finding is in contrast to tyrosine phosphorylation of the Cx43CT, as phosphorylation of Tyr 247 , Tyr 265 , and Tyr 313 is associated with decreased GJIC (10,(32)(33)(34)(35)(36). Taken together, this information suggests that phosphorylation (even by the same kinase) regulates different connexin isoforms via different mechanisms.…”
Section: Discussionmentioning
confidence: 88%
“…The surface biotinylation assay was performed following previously described methods (Li et al, 2016). Specifically, cells were plated in 10-cm tissue culture-treated dishes at 800,000 cells/dish and FAK inhibitor was added 2 h after plating.…”
Section: Surface Biotinylation Assaymentioning
confidence: 99%
“…In addition to Src, another tyrosine kinase identified to directly interact with and phosphorylate the Cx43CT was the Janus kinase family member non-receptor tyrosine-protein kinase 2 (Tyk2; [ 125 ]). Interestingly, Tyk2 can functionally substitute for Src as work from our laboratory identified that it phosphorylates Cx43CT residues Y247 and Y265 and results in concomitant loss of coupling and disassembly of gap junction plaques [ 125 ].…”
Section: Direct Interactions With Cx43 and Their Functional Conseqmentioning
confidence: 99%
“…In addition to Src, another tyrosine kinase identified to directly interact with and phosphorylate the Cx43CT was the Janus kinase family member non-receptor tyrosine-protein kinase 2 (Tyk2; [ 125 ]). Interestingly, Tyk2 can functionally substitute for Src as work from our laboratory identified that it phosphorylates Cx43CT residues Y247 and Y265 and results in concomitant loss of coupling and disassembly of gap junction plaques [ 125 ]. While phosphorylation of these sites by either Tyk2 or Src would result in disruption of the direct binding of β-tubulin and Drebrin, one difference is that Tyk2 unlikely disrupts the Cx43/ZO-1 interaction as Tyk2 does not contain a SH3 domain (for review see [ 126 ]).…”
Section: Direct Interactions With Cx43 and Their Functional Conseqmentioning
confidence: 99%